Enhancing green building teaching for architecture students through virtual reality - Dahlan, Nur Dalilah; Syed Abdullah, Sharifah Intan Sharina; Sahrir, Syazwani (Association for Computing Machinery, 2024)
As the demand for sustainable architecture increases, the education of future architects in green building practices becomes paramount. This study delves into the potential of game-based virtual reality (VR) as a trans-formative tool for teaching green building concepts to architecture students in Sichuan, China. Using a mixed-method approach, this paper compares the effectiveness of virtual reality game tutorials with traditional tutorials. From the paper findings, virtual reality games offer an immersive and engaging learning milieu, fostering a holistic understanding of green building principles and enhancing critical thinking and problem-solving skills. However, the study also highlights the need for further research to fine-tune the design process and assess the long-term impact on student learning outcomes and sustainable practices in the built environment. This research not only illuminates the benefits of virtual reality game-based learning in enhancing student engagement and knowledge retention, but also discusses content development challenges for virtual reality tutorials and prospects for international academic recognition.